The population status of pikeperch, Sander lucioperca (Linnaeus, 1758), in the Kuibyshev Reservoir (2000–2018) - V.G. Tereshchenko; F.M. Shakirova; V.Z. Latypova; N.Yu. Stepanova; O.K. Anokhina (Учёные записки Казанского университета: Серия Естественные науки)
The population status of pikeperch, Sander lucioperca (Linnaeus, 1758), in the Kuibyshev Reservoir was studied for the period from 2000 to 2018. The species is the dominant predator here. The monitoring was based on data on the dynamics of the population size and generations, as well as changes in the age structure, growth rate, and mortality. The obtained results reveal that the pikeperch population oscillated around an equilibrium state in 2000–2007. During this period, its size varied insignificantly. Subsequently, the abundance of specimens increased, and the population became even more balanced, which has been observed up to date. The index of population wellbeing in the equilibrium states has remained unchanged throughout the two decades. However, some negative tendencies have taken place over the past 10 years: an increase in the fishing pressure and a reduction in the number of older specimens in the catches. The approach used in this study should be helpful for assessing the status of fish populations, promoting sustainable fish stock exploitation under the conditions of unstable hydrological regime of reservoirs and weak control over fishing in the conservation of fish resources.